2014
DOI: 10.1149/2.0141409jes
|View full text |Cite
|
Sign up to set email alerts
|

Impurities in the Electroplated sub-50 nm Cu Lines: The Effects of the Plating Additives

Abstract: The impurities incorporated in the electrodeposited 40 nm Cu lines as well as in blanket Cu films were studied. Two different levelers were used in the study. While the impurity in the blanket films were found highly dependent on the leveler and its concentration, the leveler had no impact on the impurity in the narrow lines. Furthermore, the concentrations of suppressor and chloride showed little to no impact on the impurity in the narrow lines. An increase of accelerator concentration resulted in higher S an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Researchers at IBM [53,54] reported that the impurity content increased as a high concentration of leveler was added in the plating solution. The impurities were carbon, oxygen, sulfur, and chlorine, and their concentrations increased by about one order of magnitude (from 10 18 atoms/cm 3 to 10 19 atoms/cm 3 ) as the leveler's concentration was increased by the same order of magnitude.…”
Section: Effects Of Plating Parameter and Additive Formula On Impuritmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers at IBM [53,54] reported that the impurity content increased as a high concentration of leveler was added in the plating solution. The impurities were carbon, oxygen, sulfur, and chlorine, and their concentrations increased by about one order of magnitude (from 10 18 atoms/cm 3 to 10 19 atoms/cm 3 ) as the leveler's concentration was increased by the same order of magnitude.…”
Section: Effects Of Plating Parameter and Additive Formula On Impuritmentioning
confidence: 99%
“…Once the impurity content is high (10 18 -10 20 atoms/cm 3 , depending on the impurity type), it will significantly affect the electrical property and microstructural evolution of the Cu layer [19,21,53,54]. In this section, we will review that the impurity incorporation in the electroplated Cu layer also has a significant effect on the interfacial reactions at the solder/Cu joints.…”
Section: Effects Of Impurity On Interfacial Reactions Of Electroplatementioning
confidence: 99%
“…Organic additives are used in damascene Cu chemistries not only to achieve void-free metal filling process but also to control the impurity incorporation and grain structures of deposited Cu. The former is achieved as a result of the interplay between multiple additive components . The metal cation reduction kinetics are thus altered upon various mechanisms, such as an interaction between metal cations and additives in bulk electrolytes, the adsorption, desorption, and breakdown of a catalytic or inhibitive intermediate species adsorbed on the electrode surface, or competitive adsorption between multiple intermediates on the electrode surface. , These mechanisms at certain conditions can trigger electrochemical oscillation, where either the potential or current changes periodically within a certain range during galvanostatic or potentiostatic deposition, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of copper or tungsten CMP, film morphology, density and elemental composition change dramatically as function of thickness. [28][29][30][31][32] This is especially true in the case of copper-filled trenches of patterned wafers where topography-reducing, as well as deep trench filling additives in the electroplating bath, leave their elemental fingerprint inside the film. 28) Since film thicknesses get smaller with polish time, the above factors must also change as a function of polish time.…”
Section: Introductionmentioning
confidence: 99%